PENGARUH KEBISINGAN PRODUKTIFITAS KERJA PADA DIVISI POWER HOUSE DI PT ABC - Juliansyah, Juliansyah; Finarsita, Laesya Syifa; Nurcahya, Fauziah; Suyono, Annisa Maharani (Jurnal Ilmiah Teknik dan Manajemen Industri, 2024)
Ergonomics is essential for work efficiency and productivity, and workplace noise significantly impacts health and comfort. To reduce interference, noise sources should be eliminated. According to PMK RI No.5 of 2018 concerning Occupational Safety and Health, control of the Work Environment can be carried out in five ways, namely elimination control, and noise sources. Power House PT ABC, an important part of the pharmaceutical company, provides electrical energy to support operational activities. Field studies show workers in the power house experience emotional disturbances, impaired concentration, and ringing in the ears due to noise. This study was conducted to determine the effect of noise on work productivity at Power House PT ABC.  The data collection technique carried out in this study is using primary data by making direct observations at the Power House of PT ABC. Noise data collection was carried out using a sound level meter (SLM) tool and using questionnaires to measure work productivity at the Power House PT ABC. The data analysis technique carried out in this study used a simple linear regression test. Data processing is carried out using IBM SPSS Statistics 26 Software. The results of this study stated that there was an influence of noise on productivity as much as 93.3% with a strong relationship in the correlation between variables used in the study. The results of the linear regression equation state that noise can reduce work productivity by a constant value of -0.235 and the regression coesient number obtained can be interpreted that any increase in noise can affect work productivity by 0.046